2020
DOI: 10.1177/09727531211000040
|View full text |Cite
|
Sign up to set email alerts
|

Ayurveda Body–Mind Constitutional Types and Role of Yoga Intervention Among Type 2 Diabetes Mellitus Population of Chandigarh and Panchkula Regions

Abstract: Background: Type 2 diabetes needs a better understanding of etiological factors and management strategies based on lifestyle and constitutional factors, given its high association rate with many cardiovascular, neurological disorders, and COVID-19 infection. Purpose: The present study was undertaken to investigate the effect of Diabetes-specific integrated Yoga lifestyle Protocol (DYP) on glycemic control and lipid profiles of diabetic adults. Along with the DYP intervention, the individuals residing in Chandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A number of two studies did not specify patients' average age but were also included as an exception because the age range was provided meeting the inclusion criteria. The length of yoga intervention varied from 10 to 24 weeks with the majority of the studies receiving 12 weeks (62%) of intervention (Hegde et al, 2011 , 2020 ; Shantakumari and Sequeira, 2013 ; Datey et al, 2017 ; Sreedevi et al, 2017 ; Ranga et al, 2021 ; Sivapuram et al, 2021 ; Viswanathan et al, 2021 ) and few studies using 24 weeks (two studies: 15%) (Gordon et al, 2008 ; Sharma et al, 2020 ), 16 weeks (two studies: 15%) (Balaji et al, 2020 ; Gupta et al, 2020 ), and 10 weeks (one study: 8%) (Nair et al, 2021 ). Each yoga session lasted for 45–120 min per day, and the frequency was 1–7 days per week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of two studies did not specify patients' average age but were also included as an exception because the age range was provided meeting the inclusion criteria. The length of yoga intervention varied from 10 to 24 weeks with the majority of the studies receiving 12 weeks (62%) of intervention (Hegde et al, 2011 , 2020 ; Shantakumari and Sequeira, 2013 ; Datey et al, 2017 ; Sreedevi et al, 2017 ; Ranga et al, 2021 ; Sivapuram et al, 2021 ; Viswanathan et al, 2021 ) and few studies using 24 weeks (two studies: 15%) (Gordon et al, 2008 ; Sharma et al, 2020 ), 16 weeks (two studies: 15%) (Balaji et al, 2020 ; Gupta et al, 2020 ), and 10 weeks (one study: 8%) (Nair et al, 2021 ). Each yoga session lasted for 45–120 min per day, and the frequency was 1–7 days per week.…”
Section: Resultsmentioning
confidence: 99%
“…Practically, yoga has played a significant role in the treatment and prevention of diabetes. Several experimental studies examining the effectiveness of yoga on T2DM have shown favorable results in blood glucose, lipid profile, oxidative stress, blood pressure, anthropometric indicators, and quality of life (Gordon et al, 2008 ; Hegde et al, 2011 , 2020 ; Shantakumari and Sequeira, 2013 ; Datey et al, 2017 ; Balaji et al, 2020 ; Sharma et al, 2020 ; Nair et al, 2021 ; Ranga et al, 2021 ; Sivapuram et al, 2021 ). Additionally, favorable results were also observed in mental health, functional capacity, wellbeing, sleep quality, and body composition among patients with diabetes, as a result of receiving yoga practice (Akhtar et al, 2013 ; Innes and Selfe, 2016 ; Miles et al, 2016 ; Rshikesan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies were conducted on women ( 2 , 19 , 37 , 49 , 51 53 ), six on men ( 6 , 16 , 18 , 22 , 31 , 34 ), and the remaining studies were conducted on both genders ( 3 , 5 , 7 , 12 15 , 17 – 21 , 23 , 25 30 , 32 , 33 , 35 , 37 48 , 50 , 54 59 ). Included 37 studies had assessed BMI ( 2 , 5 7 , 12 , 13 , 15 19 , 21 , 22 , 24 , 27 – 31 , 33 , 34 , 36 38 , 40 – 43 , 46 49 , 52 , 53 , 56 58 ), 48 studies had measured TC ( 2 , 3 , 6 , 7 , 12 43 , 45 47 , 49 , 52 59 ),4 6 studies had determined LDL-C ( 2 , 3 , 6 , 7 , 12 ...…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes were reported as mean ± SD, also a meta-analysis as reported below was conducted. RCTs were performed on 11 studies with healthy situations ( 2 , 21 , 34 , 39 , 41 , 45 , 47 , 49 , 52 , 56 , 58 ), and 19 studies with type 2 diabetes mellitus ( 3 , 6 , 7 , 12 , 13 , 16 – 20 , 22 – 24 , 27 , 33 , 35 , 37 , 38 , 55 ), 10 studies with MetS ( 5 , 26 , 36 , 42 44 , 46 , 48 , 50 , 51 ), 5 studies with heart diseases (MI, CAD, CVD) ( 29 31 , 33 , 54 ), 4 studies with hypertension ( 14 , 25 , 53 , 57 ), 3 studies with chronic kidney disease (CKD) ( 15 , 28 , 59 ), 1 study with human immunodeficiency virus (HIV) ( 54 ) and 1 with obesity ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rohit Sharma and Prajapati PK have reported through a cross-sectional survey study that Vata and Kapha predominant DP, Rajasa and Tamasa predominant Manasa Prakriti (MP) are prevalent in the Type 2 diabetes population of Saurashtra region (30). Madhava S S et al reported that type 2 Diabetes majorly consists Pitta, followed by Pitta-Kapha, and Vata-Pitta DP in the study population (31). Similarly, Hetal Amin et al, through their study reported that Type-2 Diabetes mellitus is prevalent in Kapha predominant DP, Tamasa predominant MP (32).…”
Section: Dp-niddm (Non-insulin Dependant Diabtetes Mellitus)mentioning
confidence: 79%